An Interventional Study to Measure the Role of Probiotics in Treating Diarrhea in Sample of Children in Fallujah City, Iraq - Mukhlif, Zaid; Ali, Waleed Ibraheem (International Journal of Innovative Research in Medical Science, 2024)
Background: Diarrhea, a life-threatening condition in children under two years, is largely controllable with probiotics, which colonize the bowel, reducing the severity and duration of acute diarrhea. The study aims to evaluate the effectiveness and role of probiotics in treating diarrhea in children under two years old. Methods: The study is an open-label, nonblinded randomized controlled trial that followed 60 patients in Fallujah city. Patients were divided into two groups, one receiving probiotics and the other not. Treatments included oral rehydration solution, lactose-free formula, and zinc supplementation. Probiotics used were yeast-derived “saccharomyces boulardii”. The confidence level was 95%. Results: The average age of the children was 10.8 ± 5.8 months, 50% of them were males and the majority 83.3% were on milk formula. The duration of the diarrhea among the included children were significantly shorter among the group who has been given probiotics by about one day compared to other group, with adjustment to their age [B= -0.744, (95% CI: -1.455 to -0.033)]. The magnitude of probiotic treatment effect found to shorten the duration of the diarrhea by 50%. Conclusions: The study indicates that co-administration of probiotics with standard rehydration therapy reduces diarrhea duration by a mean of 1 day in children under 2 years old, and by 50%.